2002
DOI: 10.1111/j.1749-6632.2002.tb04408.x
|View full text |Cite
|
Sign up to set email alerts
|

Pheochromocytoma

Abstract: Pheochromocytoma and paragangliomas are rare tumors of chromaffin tissue that secrete catecholamines either intermittently or continuously, producing hypertension with a constellation of symptoms and signs that can be frightening to the patient and that continue to provide perplexing problems for clinicians. With surgical treatment, symptoms will be relieved and hypertension normalized or ameliorated for patients who do not have malignant tumors. Appropriate antihypertensive drugs are used to manage hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…Our aim was to analyze the effects of long-term pesticide exposure on NTs and their precursor metabolites. Studies have linked the concentration of NTs in biological fluids to various diseases, including cancerous tumors, neuroblastoma, and pheochromocytoma, common tumors in children with higher catecholamine levels in the blood and urine, as these are well-known biomarkers for diagnosing the disease and keeping an eye on treatment. In our study, it was found that blood levels of the NTs dopamine, serotonin, and norepinephrine were significantly higher in the unexposed group, as were levels of the metabolites DOPAC, 5-HIAA, and 3-MT.…”
Section: Resultsmentioning
confidence: 99%
“…Our aim was to analyze the effects of long-term pesticide exposure on NTs and their precursor metabolites. Studies have linked the concentration of NTs in biological fluids to various diseases, including cancerous tumors, neuroblastoma, and pheochromocytoma, common tumors in children with higher catecholamine levels in the blood and urine, as these are well-known biomarkers for diagnosing the disease and keeping an eye on treatment. In our study, it was found that blood levels of the NTs dopamine, serotonin, and norepinephrine were significantly higher in the unexposed group, as were levels of the metabolites DOPAC, 5-HIAA, and 3-MT.…”
Section: Resultsmentioning
confidence: 99%
“…At higher doses, esmolol inhibits β 2 -adrenoceptors located in the musculature of bronchi and blood vessels. Moreover, as patients’ oral intake improves, cardio-selective β 1 -adrenoceptor blockers such as metoprolol (Lopressor) 25–50 mg three to four times a day or atenolol (Tenormin) 12.5–25 mg once a day (occasionally twice daily) orally are also administered to control catecholamines or α-adrenoceptor blocker induced tachyarrhythmia [33,34].…”
Section: Cardiovascular Complications Related To Ppglsmentioning
confidence: 99%
“…The preferential treatment is surgery, whose preoperative preparation should include alpha1-blockers (doxazosin or prazosin) and appropriate hydration for at least 2 weeks before surgery. 52 The chronic pharmacological treatment includes alpha1-blockers, BBs (only after beginning alpha1-blockers, in the presence of symptomatic tachycardia), CCBs, ACEIs and central action agonists. 52 The paroxysmal HC of PHEO is a HE, and should be treated with SNP or injectable phentolamine and volume replacement, if necessary.…”
Section: Introductionmentioning
confidence: 99%
“… 52 The chronic pharmacological treatment includes alpha1-blockers, BBs (only after beginning alpha1-blockers, in the presence of symptomatic tachycardia), CCBs, ACEIs and central action agonists. 52 The paroxysmal HC of PHEO is a HE, and should be treated with SNP or injectable phentolamine and volume replacement, if necessary. 46 …”
Section: Introductionmentioning
confidence: 99%